2017
DOI: 10.1177/1536012117704767
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Myocardial Ischemia–Reperfusion Injury Using Sodium [18F]Fluoride Positron Emission Tomography/Computed Tomography in Rats and Humans

Abstract: Positron emission tomography (PET)/computed tomography (CT) using sodium [18F]fluoride (Na[18F]F) has been proven to be a promising hot-spot imaging modality for myocardial infarction (MI). We investigated Na[18F]F uptake in ischemia–reperfusion injury (IRI) of rats and humans. Sodium [18F]fluoride PET/CT was performed in Sprague-Dawley rats that had IRI surgery, and it readily demonstrated prominent Na[18F]F uptake in the infarct area post-IRI. Sodium [18F]fluoride uptake was matched with negative 2,3,5-triph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Results showed that glucose was accumulated abnormally in peri-infarct area in HF model group, whereas that in the sham group was intact. The abnormal increase of glucose in peri-infarct area in model group may be due to compensatory increasing glucose uptake from blood into the heart and local inflammatory response in the myocardium with low energy metabolism, which is consistent with the previous study ( Tarkia et al, 2015 ; Choi et al, 2017 ), The accumulating glucose was significantly metabolized after treatment with DQP and RSG (Figure 3B ). SUV in the model group increased by 395.15% compared with those in the sham group ( P < 0.001).…”
Section: Resultssupporting
confidence: 91%
“…Results showed that glucose was accumulated abnormally in peri-infarct area in HF model group, whereas that in the sham group was intact. The abnormal increase of glucose in peri-infarct area in model group may be due to compensatory increasing glucose uptake from blood into the heart and local inflammatory response in the myocardium with low energy metabolism, which is consistent with the previous study ( Tarkia et al, 2015 ; Choi et al, 2017 ), The accumulating glucose was significantly metabolized after treatment with DQP and RSG (Figure 3B ). SUV in the model group increased by 395.15% compared with those in the sham group ( P < 0.001).…”
Section: Resultssupporting
confidence: 91%
“…After the PET scan, a CT study was acquired and the list-mode PET data were reconstructed using a filtered back projection algorithm with CT-based attenuation correction. Images were analyzed in a blinded manner using PMOD 3.6 software (PMOD Technologies Ltd., Zürich, Switzerland), which provides the quantification of dynamic PET of the heart with a broad range of tracers in small animals including rodents [ 46 , 58 , 59 ]. In brief, volumes of interest (VOI) were drawn semi-automatically by use of a center-line within the myocardium in the projection of three dimensions (short-axis, vertical long, horizontal-long).…”
Section: Methodsmentioning
confidence: 99%
“…Sodium [ 18 F] fluoride uptake was quantitated with the standardized uptake value (SUV) over the infarct area. SUV was calculated as described previously (Choi et al, 2017).…”
Section: Sodium (Na) [ 18 F] Fluoride Positron Emission Tomography Co...mentioning
confidence: 99%